Study of the Relationship between ERCC1 Polymorphisms and Response to Platinum-based Chemotherapy in Iranian Patients with Colorectal and Gastric Cancers - Abyarghamsari, Mahdiye (Iran J Pharm Res, 2019)
This study was designed to evaluate the effect of excision repair cross complementing group 1 (ERCC1) rs11615 codon 118C/T gene polymorphisms on treatment outcomes in Iranian patients receiving oxaliplatin-based regimens for colorectal (CRC) and gastric cancers (GC). Patients, who were candidates to receive oxaliplatin-based chemotherapy, entered into the study. In 2-week intervals, the patients received combination regimen of oxaliplatin, fluorouracil, and leucovorin (FOLFOX) for 3 months. ERCC1 rs11615 codon 118C/T polymorphism was tested by restriction fragment length polymorphism polymerase chain reaction (RFLP-PCR) method using patients’ peripheral blood lymphocytes. The tumor response to chemotherapy was evaluated by examining the size of the tumor using CT scan. Association between response rates, according to the RECIST criteria, and patients’ genotypes was evaluated. Any relationship between response rate and possible explanatory factors was also determined. Overall, 40 patients (13 females (32.5%), and 27 males (67.5%)) enrolled in the study. Four patients (10.0%) carried the homozygous mutation (T/T genotype), ten patients (25.0%) were heterozygous (C/T genotype), and twenty-six patients (65%) were homozygous (C/C genotype). Response rate were 30.77%, 20.00%, and 0.00% for the genotypes C/C, C/T, and T/T, respectively. No significant association between response rate and genotypes was observed (p = 0.64). Patients with well- and moderately-differentiated histological grade of the tumor showed a better response rate (100.00% of 2 patients and 66.66% of 12 patients, respectively) compared to those with poorly differentiated (0.00% of 26 patients) histological grade (p < 0.001). Further multicenter studies are recommended to confirm conclusively our findings.